Evaluation of community pharmacy electronic patient medication record systems’ functionality focusing on safety features and alerts - Ojeleye, Oluwagbemileke Oluwabukade (2015)
Studies on electronic patient medication record (ePMR) systems that are used in community pharmacy in England have focused primarily on the ability of these systems to highlight potentially hazardous co-prescriptions and prevent clinical hazards and harm to patients. As such, there is a scarcity of literature on the use of ePMR systems, other safety functionality of the systems and user responses to alerts. This thesis aims to fill this gap by examining the functionality of ePMR systems used in community pharmacy in England, focusing on safety features and alerts. This research was conducted in England between July 2010 and July 2013. Evidence for the effectiveness of safety features and alerts in ePMR systems during the dispensing process was evaluated through a systematic review of the literature. Stakeholder perspectives of ePMR systems’ functionality were then obtained through qualitative interviews. The performance of ePMR systems licensed for the electronic prescription service (release 2) in the community pharmacy setting were then assessed using a simulated observational testing approach. Ethnographically informed observations in community pharmacies were subsequently used to study how community pharmacy professionals use ePMR systems and manage alerts in practice. The systematic review included five studies - three randomised controlled trials and two before-after studies, with drug-drug interaction (1), drug-laboratory (2), drug-pregnancy (1) and drug-age (1) alerts. The review revealed that ePMR systems in conjunction with embedded safety features are effective in picking up clinical hazards at the point of dispensing. However, there are problems of false alerts and inconsistencies in alert management. Empirical findings indicate that there are significant issues with the way ePMR systems and alerts are designed and used. Thirty participants took part in the qualitative interviews - community pharmacy professionals (13), health care policy makers (5), legal practitioners specialising in pharmacy (3), ePMR systems’ software vendors (4) and ePMR systems’ software knowledgebase creators (5). Participants attributed alert ineffectiveness in community pharmacy practice to factors such as lack of harmonisation of alert severity levels in systems, poor alert design, over-presentation of alerts and absence of management advice in alerts. Five unique ePMR systems were evaluated in eight participating pharmacies with a sixth ePMR system assessed in a demonstration setting. The systems’ performance was variable and sub-optimal. The ethnographically informed observations took place in the eight pharmacies where system assessment was conducted. The observations revealed that the current design of ePMR systems and presentation of alerts are limiting the quality of support provided to pharmacists and their support staff. This research is part of a growing body of work on the functionality of ePMR systems, their safety features and alerts indicating that ePMR systems require improvements if they are to effectively support patient safety and consistently deliver better patient outcomes. The findings highlight the need to incorporate patient context into alerting to increase alert relevance. In addition, system vendors need to make use of the evidence in the literature to design effective ePMR systems, alerts and user interfaces. An authoritative body should set the minimum specifications for ePMR systems and alerts, and identify the critical alerts that pharmacy professionals should evaluate at the point of dispensing. Additionally, training of pharmacy professionals in health information and communication technology is required to improve patient safety. This should cover areas such as informatics, human factors, safety culture, clinical decision-making, alert management, risk management and communication. Many of the findings are likely to be relevant to similar medication record systems in ambulatory pharmacies around the world; however, further work is required to understand fully the extent of the issues identified in this research.